Occurrence of plasmid linked multiple drug resistance in bacterial isolates of tannery effluent - Naraian, R.; Ram, S.; Kaistha, S. D.; Srivastava, J. (Cellular and Molecular Biology, 2012)
Effluents of three different tanneries (T-1, T-2, & T-3) were investigated to isolate and scrutinize antibiotic, chromate and salinity resistant bacteria. Total 18 isolates of 9 different bacterial genera were screened out and identified; some strains established in all effluents. Amongst the three effluents tested; T-1 exhibited largest population of all isolates compared to T-2 and T-3 effluents. The T-1 effluent contained largest 4.4 í—106 cfu/ml population of Pseudomonas aeruginosa followed by 3.9 í—106 cfu/ml in T-2 effluent. The lowest 0.7 í—106 cfu/ml count of Aeromonas spp. was recorded in T-3 effluent. Furthermore, antibiotic susceptibility tests were performed with 7 antibiotics which include ampicillin, sulfafurazole, ciprofloxacin, norfloxacin, tetracycline and amikacin. Three strains of P. aeruginosa and one strain of Escherichia coli deserved as multiple drug resistant (MDR). The P. aeruginosaT-3 and E. coliT-1 showed strongest MDR feature for 5 antibiotics. The response of chromate (50, 100, 200, 250 and 300 µg/ml) and NaCl concentrations (20, 40, 60 and 80 g/l) was incredible for 4 MDR isolates. Nearly each strain showed tolerance up to 300 µg/ml of chromate and 80 g/l of NaCl. The P. aeruginosaT-1, P. aeruginosaT-2, P. aeruginosaT-3 and E. coliT-1 were most tolerant isolates. Plasmid profiling of resistant strains was conducted with agarose gel electrophoresis. As consequence, plasmids from two strains of P. aeruginosa and E. coliT-1 represented different bands. At least for confirmation of plasmids nature; these were transformed and transformants were screened on medium having antibiotics. The study of plasmid transformation has confirmed the plasmid mediated resistance in isolates.